Cybercrime and society - Yar, Majid (SAGE, 2013)
A critical and systematic introduction, this second edition has been updated to now cover Child Pornography and Policing the Internet, making it the ideal resource for those wanting an up-to-date and authoritative account on this rapidly growing field.